Flea Burden on Rodents and Its Associated Determinants in Plague‐Endemic Localities of Karatu District, Tanzania: A Cross‐Sectional Study - Joshua Reuben Jakoniko; Apia Massawe; Elisa Daniel Mwega; Stella Thadeus Kessy (Wiley, 2024)
ABSTRACT Background Fleas infest rodents and other small mammals, serving as vectors for zoonotic diseases such as plague. This study investigates the flea burden on rodents and its associated determinants within the plague‐endemic localities of Karatu district, Tanzania. Methods A repeated cross‐sectional design was employed to capture rodents with Sherman traps in farmland, peridomestic area, bush land, and forest buffer zones across the wet and dry seasons of 2022 in plague and nonplague foci villages. Captured rodents were anaesthetized and thoroughly brushed to collect fleas, which were then identified using a dichotomous key. Results A total of 291 rodents (9 species) were captured, from which 190 fleas (4 species) were collected. The collected fleas were Dinopsyllus lypusus (46.32%), Ctenophthalmus sp (26.84%), Xenopsylla brasiliensis (16.32%), and Xenopsylla cheopis (10.53%). Approximately 38.42% of fleas were found on Mastomys natalensis, 22.63% on Lemniscomys striatus, and 18.42% on Rattus rattus. High flea abundance was recorded in farmland and peridomestic areas. The specific flea index (SFI) of X. cheopis on R. rattus was 1.0 in plague foci and <0.5 in nonplague foci. A generalized linear model revealed significant influences of rodent species, season, habitats, rodent weight, sex, and plague locations on flea abundance. Significant variation was observed between rodent sexes (p = 0.009), and a weak positive correlation existed between rodent weight and flea abundance (R = 0.17, p < 0.05). Conclusion Villages in plague foci exhibited higher abundances of fleas in comparison to nonplague foci villages. The SFI results for X. cheopis on rats in both types of villages did not surpass critical thresholds. Factors such as dry season, farmlands, and rodent characteristics influenced flea abundance on rodents in the study area.